Proving Ligand Structure-Reactivity Correlation on Multinuclear Copper Electrocatalysts Supported on Carbon Black for the Oxygen Reduction Reaction - Ponce-Hormazabal, I; Venegas-Toledo, R; Onate, R (Elsevier Ltd, 2022)
Bioinspired transition-metal catalysts seek to mimic the specific active site of metalloenzymes, as the multicopper oxidase, that can efficiently reduce dioxygen to water via a complete 4-electrons mechanism at low overpotential. However, the multicopper oxidase enzymes lack stability under operando conditions, hampering their application in fuel cell electrodes. Bioinspired multicopper catalysts present a remarkable electrocatalytic activity for the oxygen reduction reaction (ORR), where the structure and electronic properties of the ligands play a fundamental role. In this work, we explore the instantaneous catalytic activity and its evolution under operando conditions of two multicopper catalysts with different ligand flexibility, pyridyl ligand (CuL1), and pyridylmethyl ligand (CuL2), by conventional electrochemical techniques and scanning electrochemical microscopy (SECM). Both catalysts present similar instantaneous electrocatalytic activity with no significant role of the ligand, but there is a change in the mechanism. While the rigidity of CuL1 reduces the dioxygen via direct 4e-, the catalyst with higher flexibility (CuL2) follows a 2e−x 2e− mechanism. The production of H2O2 as ORR byproduct evaluated by rotating ring-disk electrode (RRDE) and stability test evaluated under ORR operating conditions by SECM imaging of both catalysts demonstrated a higher decrease in catalytic activity and higher H2O2 production in CuL2 than in CuL1, which evidences a ligand structure-reactivity correlation. These results contribute to the rational design of next generation of copper catalysts and open the door to a new methodology to evaluate the activity evolution under operando conditions by SECM. © 2022